PENGARUH PROFITABITAS, GROWTH OPPORTUNITY, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN SEBAGAI VARIABEL KONTROL (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2017) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
Companies that have go public in general are trying to increase investorprosperity through corporate value which is an investor's perception of the level ofsuccess of the company. One method used to analyze the firm value uses the price to bookvalue ratio (PBV). This study aims to determine the effect of profitability, growthopportunity, capital structure, and liquidity on firm value with the size and age as acontrol variable in all the companies listed on the Stock Exchange in the period 2015-2017 which amounted to 543 companies.The research method used is descriptive analysismethod using regression analysis and data analysis used, namely multiple linear analysis.The sample in this study was 191 companies carried out by purposive samplingtechnique. The statistical test used is the IBM SPSS 25 program.The results of theanalysis show that profitability, growth opportunity, capital structure have a significantinfluence on firm value. While liquidity does not have a significant effect on firm value.Keywords : Profitability, Growth Opportunity, Capital Structure, Liquidity, CompanySize, Company Age, Company Value